2022
DOI: 10.1159/000518121
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Suppresses the Progression of Colorectal Cancer by Improving Immunogenic Cell Death Caused by Irinotecan

Abstract: <b><i>Background:</i></b> Irinotecan (IRI) is a common chemotherapeutic drug for colorectal cancer; however, the mechanism underlying its immunomodulatory effect remains unclear. Curcumin (CUR), an adjuvant drug with anti-inflammatory and antitumor effects, has been studied extensively, although its synergistic antitumor effect remains unclear. <b><i>Methods:</i></b> The effects of CUR and IRI on oxidative stress and their antitumor effects were detected by flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Apoptosis was alleviated after interfering with the CHOP gene. Zhu C et al (2022) separately demonstrated a similar effect of curcumin on CRC cells CT-26.…”
Section: Chinese Botanical Drug Extracts Against Digestive System Tum...mentioning
confidence: 79%
“…Apoptosis was alleviated after interfering with the CHOP gene. Zhu C et al (2022) separately demonstrated a similar effect of curcumin on CRC cells CT-26.…”
Section: Chinese Botanical Drug Extracts Against Digestive System Tum...mentioning
confidence: 79%
“…ICD is widely recognized as a crucial component for effective cancer immunotherapy. Several studies have indicated that CUR can induce ICD through autophagy [ 35 38 ]. The process of ICD involves the release of damage associated molecular patterns (DAMPs), including CRT, ATP, and HMGB1.…”
Section: Resultsmentioning
confidence: 99%
“…One such agent may be curcumin, a polyphenolic compound found in the yellow spice turmeric. Curcumin has been found to possess anti-inflammatory, 36 anti-angiogenesis, 37,38 anti-cancer -39,40 and anti-oxidative 41 properties. It has been studied as a form of treatment [42][43][44] for various cancer types, including highly treatment-resistant cancers.…”
Section: Discussionmentioning
confidence: 99%